Antithrombotic activities of Newbouldia laevis (P. Beauv) seem. ex Bureau leaves - Chinaka O. Nwaehujor, Rita I. Udegbunam, Julius O. Ode, Stella A. Madubuike (Journal of Applied Pharmaceutical Science, 2015)
The study evaluated anticoagulant properties of the methanol extract of Newbouldia laevis leaves using blood clotting time, bleeding time and thrombin-induced clotting assay as standard procedures. Oral acute toxicity studies showed that the extract had a high safety margin, up to 2000 mg/kg in Wistar rats. The methanol leaf extract of N. laevis significantly (p
Keywords: Anticoagulant, Newbouldia laevis, Heparin, Ethylenediaminetetraacetic (EDTA), Thrombosis, Thrombin-induced clotting time.